Observations of HF-induced instability in the auroral E region - Schlatter, Nicola M.; Ivchenko, Nickolay; Gustavsson, Björn Johan; Leyser, Thomas; Rietveld, Michael T (Annales Geophysicae, 2013)
Enhancements were observed in backscattered radar power during an ionospheric heating experiment from two distinct altitude regions in the auroral E region above Tromsø. For the experiment the EISCAT Tromsø heater was operated with O mode and X mode alternated at 4.04 MHz, close to the 3rd electron gyroharmonic. Ion-line data recorded with the EISCAT UHF radar reveal different temporal evolutions as well as different ion-line characteristics for the enhancements from the two altitude regions. The upper layer is dominated by a strong central feature, whereas the lower layer has three peaks corresponding to the central feature and the two ion lines. The altitude region of the two closely spaced (altitude separation 5 km) but distinct enhancements is close to the critical altitude for the heater wave.